Viabilidad y tasa de preñez de embriones producidos in vitro a partir de semen sexado comparado con semen convencional en Bos taurus y Bos indicus (2018)
The study was carried out with the in vitro embryo production of the In Vitro Colombia® laboratory of 2015. The embryo cleavage rate, the in vitro embryo production (IVP) and the pregnancy rate were analysed based on the type of semen used (sexed and conventional) for fertilization and on the bovine species (Bos taurus, Bos indicus). Data from 840 sessions of follicular aspiration were analysed, resulting in 127 503 oocytes placed in in vitro culture from 5257 females. The embryonic cleavage rate for sexed semen was 69.6% and for conventional semen 74.5% (p<0.001). It was obtained 20.8% of IVP for sexed semen and 26.5% for conventional semen (p<0.001). The sexed semen of B. taurus performed better in terms of embryonic cleavage than that of B. indicus (71.1 and 64.4%, respectively (p<0.001), whereas the conventional semen of B. indicus performed better than B. taurus (76.0 and 70.3%, respectively, p<0.001) In the IVP the sexed semen of B. indicus performed better than the semen of B. taurus (21.5 and 20.7%, respectively, p=0.008), whereas with conventional semen the IVP of B. indicus was 28.2% compared to 22.2% of B. taurus (p<0.001) .There were no significant differences for pregnancy rates. It is concluded that the use of sexed semen to produce in vitro bovine embryos is viable. © 2018 Universidad Nacional Mayor de San Marcos. All Rights Reserved.